An evaluation of junior doctors’ experience in smoking cessation training in a rural mental health setting - Faint, Nicholas; Cuesta-Briand, Beatriz; Coleman, Mathew (Frontiers in Psychiatry, 2022)
Introduction Smoking prevalence remains high amongst people with mental illness, however, they are less likely to be screened for tobacco dependence and offered treatment to quit. Smoking cessation and education training are insufficient in medical schools, despite a positive relationship between training and practice once qualified. However, the question as to whether there is adequate skill and expertise to address smoking in people with mental illness within Australian mental health settings is unclear. Furthermore, people living in rural and remote areas smoke at higher rates, quit at lower rates than those in urban areas, and experience limitations in their ability to access smoking cessation supports. The Smokers’ Clinic is an initiative established in a rural Australian mental health service offering a smoking cessation service to patients and staff employed by the service. Aim This study aims to assess the change in the knowledge and confidence of resident medical officers in their understanding of nicotine dependence, smoking cessation strategies and prescribing nicotine replacement therapy in a community mental health setting. It was hypothesized that providing education and supervised clinical experience would improve knowledge, increasing confidence and motivation in managing smoking cessation in mental health patients. The research was undertaken using data collected through a questionnaire obtained from surveying resident medical officers administering the Smokers’ Clinic following a 10-week rural community mental health rotation. Materials and methods Twenty resident medical officers completed the 10-week rotation, with 14 completing the questionnaire. Knowledge of tobacco smoking, nicotine dependence and smoking cessation interventions improved with the experience of the Smokers’ Clinic during the clinical rotation. Resident medical officers were motivated to spend additional time engaged in self-directed learning and all reported continued use of acquired experience and information in their clinical work after the rotation. Conclusion This study indicates the utility of a novel approach in delivering education, training, building clinical expertise, and facilitating sustained clinical capacity amongst junior medical staff for smoking cessation in a rural community mental health setting. It offers an efficient approach for mental health services to deliver smoking cessation services to reduce the morbidity and mortality burden associated with tobacco smoking.